ERp57 Functions as a Subunit of Specific Complexes Formed with the ER Lectins Calreticulin and Calnexin - Oliver, Jason D. (The American Society for Cell Biology, 1999)
ERp57 is a lumenal protein of the endoplasmic reticulum (ER) and a member of the protein disulfide isomerase (PDI) family. In contrast to archetypal PDI, ERp57 interacts specifically with newly synthesized glycoproteins. In this study we demonstrate that ERp57 forms discrete complexes with the ER lectins, calnexin and calreticulin. Specific ERp57/calreticulin complexes exist in canine pancreatic microsomes, as demonstrated by SDS-PAGE after cross-linking, and by native electrophoresis in the absence of cross-linking. After in vitro translation and import into microsomes, radiolabeled ERp57 can be cross-linked to endogenous calreticulin and calnexin while radiolabeled PDI cannot. Likewise, radiolabeled calreticulin is cross-linked to endogenous ERp57 but not PDI. Similar results were obtained in Lec23 cells, which lack the glucosidase I necessary to produce glycoprotein substrates capable of binding to calnexin and calreticulin. This observation indicates that ERp57 interacts with both of the ER lectins in the absence of their glycoprotein substrate. This result was confirmed by a specific interaction between in vitro synthesized calreticulin and ERp57 prepared in solution in the absence of other ER components. We conclude that ERp57 forms complexes with both calnexin and calreticulin and propose that it is these complexes that can specifically modulate glycoprotein folding within the ER lumen.